A Community Arts Program for Underserved Children: Getting Things Done and Member Development - Sang-Hie Lee (Ital Publication, 2020)
The Program: The AmeriCorps ArtsUSF program was a federally funded outreach program that provided hands-on arts experience to underserved children in culturally and economically deprived communities in and around a large metropolitan area. The project had two components: Getting Things Done (GTD) and Member Development (MD). Objectives: The goals of GTD were to help improve the communities' self-image, stability, and culture by providing accessible, safe, and affordable cultural activities and programs. The goals of MD were to help the AmeriCorps volunteer artist-teacher members develop an awareness of societal problems, teaching and class management skills, and to become responsible citizens. Methods: GTD goals were measured using a quantitative survey instrument developed for the program. Pre (November) and post (May) data were compared using paired one-tailed t-tests to see if there were significant changes. MD outcomes were summarized from content analysis of member journals. Results: Data showed progress in all measured items, particularly, integrating arts to life, group problem-solving skills, attitude on diversity, and attitude on being-kind-to-each-other. Factor analysis results demonstrated strong connections among arts skills, expression through the arts, art appreciation skills, and integrating arts to life. There was an association among class learning skills, attitude on diversity, and attitude on being kind-to-each-other. Independent problem-solving skills were associated with expressive skills through the arts, integrating arts to life, attitude on diversity, and class learning skills. In the post data, independent problem-solving skills were further related to anti-drug, alcohol, and smoking attitude, and art skills. Members expressed that AmeriCorps ArtsUSF experience provided a life-changing impact on them. Seeing the effects of their input on other, they realized that one way of achieving the American dream was by helping others. Conclusion: The program gave a sense of pride and ownership to the underserved communities, and the experience gave the artist-members the confidence and self-esteem necessary to pursue their own life's goals. Novelty: Federally funded, community-wide supported program with novel program and curriculum. Improvement: The initial phase could be better organized and more affective narratives could be added in the survey instrument.